1957
DOI: 10.1139/y57-080
|View full text |Cite
|
Sign up to set email alerts
|

The Reason for the Shape of the Distensibility Curves of Arteries

Abstract: It is characteristic of arteries that they do not obey Hooke's law, but resist further stretch more strongly, the more they are stretched. It appears that this might be due to the combination of elastin fibers in the elastic laminae, with the much less distensible collagenous libers in the media and adventitia, more and more of which reach their 'unstretched length' as distension is increased. This has been verified on human iliac arteries, from autopsy, by comparing the 'elastic diagrams' (tension vs. circumf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
254
1
7

Year Published

1983
1983
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 365 publications
(281 citation statements)
references
References 6 publications
19
254
1
7
Order By: Relevance
“…The stress-strain response was nonlinear, characteristic of many tissues (Fig. 3) [27]. As expected, anisotropic behavior was observed in the tensile strength of the tissue.…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…The stress-strain response was nonlinear, characteristic of many tissues (Fig. 3) [27]. As expected, anisotropic behavior was observed in the tensile strength of the tissue.…”
Section: Resultssupporting
confidence: 63%
“…Biaxial samples (n ¼ 9), as with uniaxial samples, exhibited a nonlinear stress-strain response, characteristic of biological tissues (Fig. 3(b)) [27]. As all samples exhibited similar nonlinear behavior, it is reasonable to consider the mean response ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…22 Roach and Burton have demonstrated that under very low pressure or stress, the elastic modulus of the arterial wall is very close to the elastic modulus of elastin alone, because little or no collagen bears stress under this condition. 23 Cox has shown a significant correlation between the initial slope of the stress-strain curve at zero stress and the elastin content. 24 The mean elastic modulus of elastin (E inc at 0 stress) in this study was approximately 1.0ϫ10 6 dyne/cm 2 .…”
Section: Bank Et Al Brachial Artery Elasticity 45mentioning
confidence: 99%
“…While further studies need to be done to define changes in elastin composition, mechanical data indicate changes in the ECM composition and structure. 28 Oxygen was most deficient in constructs cultured using 11% O 2 conditions and resulted in the least cell migration of all conditions. These 11% O 2 conditions further decreased the amount of available oxygen deep within the construct resulting in cells remaining on the surface without significant migration.…”
Section: Discussionmentioning
confidence: 97%